Optimalisasi Website Sekolah sebagai Pusat Informasi melalui Integrasi Direktori Alumni dan Struktur Organisasi MA Darul Hikmah - Muhamad Khaerul Umam; Naufal Muhammad Raekhan; Putri Maharani Fetra; Elrahma Nazwa Fitria Lesmana; Arif Indra Pratama; Fathur Khairan Ramadhan; Ihsan Ghifari Najito; Ranggi Febrian; Muhammad Dzakwan Fadhlurrohman; Tutur Handayani Malau (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The development of information technology requires educational institutions to have informative and interactive digital portals. This community service aims to optimize the MA Daarul Hikmah website as an effective information center by integrating alumni directory features and a dynamic organizational structure. The implementation methods included needs analysis, website development assistance, content management training, and implementation of new features. The results of the activity showed a transformation of the website from a static and basic one to a dynamic, responsive information platform with two main features: (1) an Alumni Directory that allows alumni to register and connect, and (2) an Organizational Structure Page that displays the profiles and main tasks of each work unit. An evaluation through a user satisfaction questionnaire (teachers and staff) showed a significant increase in ease of access to information and perception of school transparency. The conclusion of this activity is that website optimization has succeeded in creating a more transparent means of communication, strengthening the alumni network, and enhancing the school's digital image. A sustainable recommendation is to form a website management team and provide regular training to ensure continuity of information updates.